2024
DOI: 10.5620/eaht.2024017
|View full text |Cite
|
Sign up to set email alerts
|

Abundance, characterization, and health risk evaluation of microplastics in borehole water in Birnin Kebbi, Nigeria

Tajudeen Yahaya,
Mutiyat Kehinde Adewale,
Abdulgafar Bala Ibrahim
et al.

Abstract: Microplastic pollution has become a global menace, and water, being a major "sink" for pollutants, represents a significant source of human exposure. This study aimed to assess the safety of borehole water in Birnin Kebbi, Nigeria, specifically concerning microplastic pollution. Water samples were collected from boreholes in selected areas, including Bayan Kara, Malali, Rafin Atiku, Aliero Quarters, GwadanGaji, FUBK Takeoff Site, Kalgo Market, and Tarasa. Microplastics were extracted from the water samples thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
1
0
0
Order By: Relevance
“…It is noteworthy that the characteristics of the experimental microplastics were similar to those of microplastics detected in the environment of the study area, as revealed in a study on microplastics abundance and characteristics in borehole water in the city by Yahaya et al [ 60 ]. This suggests that the effects observed in the experimental animals are likely to occur in animals exposed to microplastics in the environment.…”
Section: Discussionsupporting
confidence: 71%
“…It is noteworthy that the characteristics of the experimental microplastics were similar to those of microplastics detected in the environment of the study area, as revealed in a study on microplastics abundance and characteristics in borehole water in the city by Yahaya et al [ 60 ]. This suggests that the effects observed in the experimental animals are likely to occur in animals exposed to microplastics in the environment.…”
Section: Discussionsupporting
confidence: 71%